1997
DOI: 10.3354/ame012177
|View full text |Cite
|
Sign up to set email alerts
|

Oligotrophy and pelagic marine bacteria: facts and fiction

Abstract: Oligotrophy, or the inability of bacterial cells to propagate at elevated nutrient concentrations, is a controversial phenomenon in microbiology. The exact cause of the unculturability of many indigenous marine bacteria on standard laboratory media has still not been resolved. Unfortunately, the physiology of such cells is difficult to investigate as long as high cell density cultures cannot be obtained. An extensive evaluation of experiments relating to oligotrophy and the cultivation of marine bacteria is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 98 publications
5
125
0
4
Order By: Relevance
“…The diversity of culturable cells varied greatly, depending on the culture media used for their detection. Similar trends were found by Schut et al (1997). The combination of both R2Am and MA media appeared to allow the isolation of the highest number of strains.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The diversity of culturable cells varied greatly, depending on the culture media used for their detection. Similar trends were found by Schut et al (1997). The combination of both R2Am and MA media appeared to allow the isolation of the highest number of strains.…”
supporting
confidence: 70%
“…Several media with different compositions have been proposed for isolating new species (Martin & MacLeod 1984, Gonzalez & Moran 1997) and a dilution culture technique has been developed to isolate oligotrophic species, which do not grow on nutrient-rich medium . However, culturability is also a function of the physiological state of a cell, and cells of cultured species may become unculturable under adverse environmental conditions (Schut et al 1997). Recent studies have demonstrated that, even if the CFU proportion remains very low, cultured species sometimes represent a significant part of the community DNA (Pinhassi et al 1997).…”
mentioning
confidence: 99%
“…Obligate oligotrophy has been proposed as a key factor leading to poor recovery of environmental microorganisms in pure cultures (19)(20)(21), and our study provides clear evidence for the predominance of a copiotroph lifestyle among existing marine cultures across taxonomic groups. Our data also suggest that oligotroph characteristics in surface ocean bacteria are not limited to members of Prochlorococcus and Pelagibacter in tropical regions, as previously thought (16,22), but rather is a common trophic strategy among many bacterioplankton lineages around the globe.…”
Section: Resultsmentioning
confidence: 71%
“…There is increasing evidence that defense against grazing (14,17) and antiphage defense systems (43) are important survival strategies of bacteria in aquatic systems. Nonetheless, an thorough assessment of life history traits has not been often performed for marine bacteria 20 except for isolates (33).…”
Section: Introductionmentioning
confidence: 99%